Teaching Arabic Through Social Media at Al-Azhar Institute Pare Kediri - Moh Aziz Arifin; Uril Bahruddin (Alsuna: Journal of Arabic and English Language, 2021)
Purpose - This research stems from the problem of the difficulty of learning the Arabic language, and the reason may be due to the lack of benefit from the social media that is now open. This is research aims to (1) to know the teaching of Arabic through social media at Al-Azhar Institute Pare Kediri (2) to know the lack and advantages of teaching Arabic through social media at Al-Azhar Pare Kediri Institute. Design/methodology/approach - The research design is descriptive-qualitative research. The data gained are written words and sentences from the novel that imply an educational value. Findings - The results of this are research that learning Arabic through social media in Al-Azhar is not organized. Well, because learning using social media is not included in the objectives of learning Arabic at Al-Azhar Institute Pare Kediri. On the other hand, to participate in online learning, Al-Azhar Institute Pare Kediri opens the program through Zoom application instead of social media; (2) Knowing the advantages of learning through social media at Al-Azhar Institute Pare Kediri is like an institution that has many Arabic language learning programs. As for the lack of learning Arabic through social media in Al-Azhar, social media has not been used optimally for Arabic language learning programs. Originality/value - The use of social media at al-Azhar Institute Pare Kediri in the Arabic learning process is still not used optimally. Paper type – Research paper